EKSPLORASI PENGALAMAN TERHADAP RISIKO BERWISATA PADA KONSUMEN WISATA PEREMPUAN DI INDONESIA - Made Handijaya Dewantara; Peni Zulandari Suroto; Maria Zefanya Sampe (Journal of Tourism Destination and Attraction, 2020)
This study aims to explore the experiences of Indonesian female tour consumers regarding risks they face when traveling domestically. Data was collected through focus group discussions (FGD), to nine female tour consumer informants who traveled in Indonesia. Qualitative data were analyzed descriptively. The opposite grouping of keywords is done by creating a code and make narration. The results showed that there were four motivations for traveling, and two of them were related to risk. Female tour consumers want to explore new destinations, have high sense of curiosity, are interested in enjoying natural, cultural, and culinary richness. Forms of risk experienced by female tour consumers include natural conditions, geography, racial discrimination, verbal harassment, and physical injury. Female tour consumers anticipate risks by looking at various references, for making decisions, travel partners, and seeing publications from trusted sources. Although index and risk management have not been standardized in Indonesia, due to a travel ban in a cultural context, Indonesian female tour consumers tend to take risks to travel and repeat it several times. Behind the risk, they get important things such as unbeatable views, new experiences and knowledge, excitement, satisfying curiosity, and enjoyment of local wisdom. The findings on Indonesian female tour consumers are important input for tourism destination stakeholders.